Oxygen Isotopic Composition of the Surface Snow in Mizuho Plateau - Kato, K.; Watanabe, O.; Satow, K. (1978)
P(論文) Oxygen isotopic compositions of new-fallen snow collected at Syowa Station, and drifting snow at Mizuho Camp and various stations in Mizuho Plateau were determined. Daily variation of oxygen isotopic composition of new snow at Syowa Station is caused mainly by the supply of ^<18>O-rich water vapor according to the approach of a cyclone. Seasonal variations of oxygen isotopic compositions of new snow at Syowa Station and of drifting snow at Mizuho Camp are controlled not only by the seasonal variation of atmospheric temperature, but also by that of transportation process of water vapor to Syowa Station and Mizuho Camp varying with the distance from the coast of open sea. Oxygen isotopic compositions of drifting snow at the stations at elevations below 1000m are almost independent of elevation. At elevations between 1000 and 2900m, oxygen isotopic compositions of drifting snow against elevation show a fairly linear relationship. At elevations between 3200 and 3300m, a large anomaly is found in the variation with elevation of oxygen isotopic composition of drifting snow. The area where the anomaly is found is considered to be the boundary between the spheres of influence of maritime cyclone and Antarctic anticyclone. The drifting snow does not reflect the daily variation of meteorological condition and is of relatively local origin. departmental bulletin paper